(untitled) (International journal of artificial intelligence, 2025)
The article discusses the issues of personal development in the context of the use of modern pedagogical technologies. The author analyzes the influence of the educational environment, digitalization and innovative teaching methods on the formation of a student's personality. Special attention is paid to the role of the teacher as a facilitator of personal growth, as well as the conditions that ensure the self-realization and self-development of students.